X-ray and theoretical investigation of (Z)-3-(adamantan-1-yl)-1-(phenyl or 3-chlorophenyl)-S-(4-bromobenzyl)isothioureas: an exploration involving weak non-covalent interactions, chemotherapeutic activities and QM/MM binding energy. Issue 6 (13th April 2022) - Al-Omary, Fatmah A. M.; Chowdary Gude, Nikhila; Al-Rasheed, Lamees S.; Alkahtani, Hamad N.; Hassan, Hanan M.; Al-Abdullah, Ebtehal S.; El-Emam, Ali A.; Percino, M. Judith; Thamotharan, Subbiah
Abstract: A detailed exploration of crystal packing of two adamantane-isothiourea hybrid derivatives along with a known closely related structure has been performed to delineate the effect of halogen substituents and the role of weak intermolecular interactions in their supramolecular architectures. The adamantane-isothiourea hybrid derivatives used in the present study are ( Z )-3-(Adamantan-1-yl)- S -(4-bromobenzyl)-1-phenylisothiourea (1 ), C24 H27 BrN2 S and ( Z )-3-(Adamantan-1-yl)- S -(4-bromobenzyl)-1-(3-chlorophenyl)isothiourea (2 ), C24 H26 BrClN2 S, characterized by X-ray crystallography. The X-ray structures revealed that the molecular conformation of 1 and 2 are different and stabilized by intramolecular C–H···N interactions. In addition, a short intramolecular H···H contact is formed in 2 . The Hirshfeld surface analysis was used to delineate the nature of different intermolecular interactions and their contributions toward crystal packing. The quantitative analysis of strengths of molecular dimers existed in 1 and 2 has been performed using the PIXEL method. The electrostatic potential map clearly revealed nature and strength of σ-holes at Br and Cl atoms. The topological analysis was used to characterize the nature and the strength of various intermolecular interactions including the type I Br···Br contact. Interestingly, all the H–H bonding observed in 1 and 2 show closed-shell in nature. Further, an in-vitro antimicrobial activity studies suggest that the title compounds exhibited potent antibacterial activity against all the tested Gram-positive bacterial strains and Gram-negative Escherichia coli . Compound 2 showed marked anti-proliferative activity against MCF-7 and HeLa cell lines. Communicated by Ramaswamy H. Sarma